Penegakan Hukum Terhadap Tindak Pidana Korupsi Dalam Pembangunan Balai Benih Induk (BBI) Di Kabupaten Nias Selatan (Studi Putusan No.116/Pid.Sus-Tpk/2014/PN.Mdn) - Donny Christian Harita; Taufik Siregar; Arie Kartika (JUNCTO: Jurnal Ilmiah Hukum, 2020)
Corruption is an extraordinary crime that is contagious in every state apparatus, both in the central government and regional governments. The research method in this paper is a normative method that collects library data, namely legislation, law books, judges' decisions, mass media and scientific journals related to the issues discussed in this thesis. Law enforcement of corruption in Indonesia as outlined in the Law of the Republic of Indonesia Number 20 of 2001 concerning Amendments to the Law of the Republic of Indonesia Number 31 of 1999 concerning Corruption Eradication is a representation of 3 elements of law enforcement, namely the lawmaking element (making this law), the element of law enforcement officers namely this law also regulates law enforcement officers for example with the Corruption Eradication Commission and the elements of the community environment by regulating public participation in eradicating corruption in Indonesia. Judge's consideration in dropping the verdict Number: 116 / Pid.Sus-TPK / 2014 / PN.Mdn is to consider mitigating and aggravating matters, taking into account the defendant's ability to take responsibility, considering the absence of forgiving and justifying reasons.